Study on the Relationship Between Groundwater Depth and Land Use Change Based on Indicator Kriging Method - XU Yueyue; SU Tao; LEI Bo; WANG Lei (Renmin Zhujiang, 2021)
It is very important to study the temporal and spatial variation of groundwater depth for the rational development and utilization of groundwater resources,the promotion of crop growth and the prevention and control of land salinization.Taking Jiefangzha of Hetao Irrigation Area as the research area,this paper analyzes the spatial-temporal variation of groundwater depth in different irrigation periods by the indicator Kriging interpolation,and explores the relationship between different groundwater depth and land use type change with land use type classification map.The results show that:①The annual variation of groundwater depth in the Jiefangzha irrigation area presents a double-peak curve.The minimum value appears in May and June,while the maximum value appears in August and September.On the whole,the groundwater depth in the irrigation area shows an increasing trend in each year,and the groundwater depth gradually increases from southwest to northeast,with the characteristics of shallow buried area increasing and deep buried area decreasing;②The groundwater depth changes from 1.82 m to 1.99 m,which is conducive to the stable growth of cultivated land,forest and grassland in irrigation area.From the perspective of regional ecological environment change,when the groundwater depth is greater than 2 m,there is an adverse transformation of land degradation.